Analysis of the Implementation of Radiation Occupational Safety and Health Management Systems in Radiology Installations: An Empirical Study at Regional General Hospitals in Banyumas Regency - Asri Indah Aryani; Oktia Woro; Agus Hermanto; Titi Prihatin; RSE Pujiastuti (Universitas Negeri Semarang, 2023)
Objective from study This is analyze application system management safety and health Work radiation on installation radiology at the district hospital Banyumas . Type research used _ in study This is study method mix . Data validation is carried out with use technique triangulation , that is triangulation sources and data. Triangulation source done with method check the data obtained through a number of source . Based on results and discussion can concluded that power in work units district hospital radiology Banyumas has 2 (two) Specialists Radiology , 1 ( one ) officer Protection Radiation and 5 (five) Radiographers Diploma three . In accordance with Regulation Head of the Nuclear Energy Regulatory Agency Number 8 of 2011. There are 5 variables tested in application System Management Occupational Safety and Health Radiation On Installation Radiology . From fifth variable Licensing , management requirements , requirements security , requirements technical and testing security of the 14 processed components (50 points ) 25 points (50.34%) were fulfilled standards / regulations . A total of 11 points (22.45%) were met , however No in accordance with standard . Limitations Focus study This only on one House sick , so the analysis limited . Moment researching more further , preferably use more from one item for can compare result .